PARP7 protects the lung epithelial barrier from diverse environmental threats - Devon Jeltema; Kun Yang; Joshua J. Baty; Antonina Araszkiewicz; Cong Xing; Kennady Knox; Zhen Tang; Nicole Dobbs; Nan Yan (Proceedings of the National Academy of Sciences, 2026)
Poly-ADP-ribose polymerase (PARP) family proteins are involved in a wide range of cellular processes. Several PARPs are targeted by inhibitors as treatments for cancer based on their biochemical functions; however, the physiological functions of most PARPs and the potential adverse effects of PARP inhibition are unknown. Here, we show that PARP7 is important for lung physiology. Loss of PARP7 in mice increases susceptibility to chemically induced diffuse alveolar hemorrhaging (DAH) and pristane-induced lupus. Single-nucleus RNA-seq reveals that PARP7 is selectively expressed in alveolar type I cells and PARP7 loss increases immune cell infiltration within the lung, indicating a loss of epithelial barrier integrity. Further, PARP7 inhibition in human bronchial epithelial cells in air–liquid interface culture leads to increased barrier permeability after cigarette smoke challenge or bacterial infection. Mechanistically, we show that PARP7 target, aryl hydrocarbon receptor (AHR), mediates diverse cellular responses to cigarette smoke challenge, including loss of tight junction protein Occludin and increased expression of xenobiotic metabolizing genes and proinflammatory genes. Together, our study uncovers PARP7 as a key player in maintaining the epithelial barrier integrity within the lung, which may have important implications for pulmonary diseases and for guiding PARP7 inhibitor use in the clinic.